The Effect of Organic Fertilizers on Morphological Traits, Essential Oil Content and Components of Basil (Ocimum basilicum L.) - Mahdi Rahmanian; Behrooz Esmaielpour; Javad Hadian; Malek Hossein Shahriari; Hamideh Fatemi (Journal of Agricultural Science and Sustainable Production, 2017)
The useage of organic fertilizer in a sustainable agricultural system could reduce the environmental risks associated with the use of chemical fertilizers by improving the physical, chemical and biological properties of soils that will result in sustainable production. Therefore, it seems necessary to assessing the impact of organic fertilizers on growth and yield of crops. In this study, an experiment was conducted in a completely randomized design,University of Mohaghegh Ardabili to evaluate the effect of organic fertilizers including vermicompost and spent mushroom compost on morphological traits and essential oil of basil. Treatments included zero (control), 10, 20, 30, 40 and 50 percent of vermicompost and spent mushroom compost in both washed and unwashed cases. The results of this study showed thatthe maximum of fresh weight of bush, leaves numbers, leaf area, leaf dry weight, number of main stems and chlorophyll were observed in plant cultivation medium supplemented with 30 and 40 percent of washed spent mushroom compost that were significantly more than the control treatment. While, the major amount of plant were height and bush dry weight, stem dry weight, root fresh and dry weight and percent of essential oil were recorded in treatments containing 20 and 30% of vermicompost. The results showed that the use of organic fertilizers increased essential oil composition in basil. So that the highest percentage of myrcene, beta-pinene, eugenol and gama-muurolene were obtained in plants grown in substrate containing different percentages of washed mushroom compost. In this study on the most traits, the use of organic fertilizers showed a significant effect compared to the control.